Evaluation on subcritical water extraction of phenolic compounds from Chlorella sp. Microalgae - Zakaria, Siti Maisurah (2019)
Chlorella sp. microalgae are considered to be an important functional food and a source of nutrients due to their abundance and positive health effects. This study focused on utilization of green solvent as alternative to replace chemical solvent that conventionally used to extract phenolic compounds from microalgae for food and health purposes. Subcritical water extraction (SWE) is the best alternative for this purpose. The use of pressurised hot water and high temperature during the subcritical phase allows the dielectric constant and polarity of water to be modified, which then contributes to an improved extraction process. The extraction of phenolic compounds was studied at different temperatures (100-300°C), times (5-30 min) and solid loading (5-30 wt.%). Results from SWE experiments have shown that this technique has recovered a higher value of phenolic compounds (58.45 mgGAE/g) and antioxidant activity (67.03%) with a lower extraction time (up to 20 min) when compared to conventional soxhlet method using methanol with only 36.46 mgGAE/g phenolic content and 54.83% of antioxidant activity. The release of phenolic compounds into the subcritical water resulted in a mixture of phenolic acids (ferulic, caffeic and ρ-coumaric acids), and these acids showed significant antioxidant properties. The results showed the acid release began during the initial heating up stage at higher temperature. Using response surface methodology, the optimal operating conditions for the extraction process were found; 5 min at 163 °C with 20 wt.% of solid loading resulting in products with 58.73 mgGAE/g total phenolic content and 68.5% antioxidant activity. The phenolic content was also highly correlated (R² = 0.935) with the antioxidant capacity. Kinetic studies have revealed that the extraction from Chlorella sp. microalgae using subcritical water treatment followed first order kinetics and the extraction was dependent on temperature. As a result of the increasing temperature, a rising trend in the estimated values of the mass transfer coefficient, k, was observed. . The activation energy, Ea, was calculated as 11.146 kJ/mol for the extraction treatment. The value of thermodynamic activation parameters (ΔS ≠, ΔH≠, ΔG≠) are affected by increasing the water temperature, which related to an increase of extraction activity at higher temperature. The findings from this study demonstrated that Chlorella sp. extracts possessed a strong antioxidant activity. They also highlighted the potential application for subcritical water, as a green approach, that is able to produce high quality extracts from Chlorella sp. as a source of natural bioactive compounds for the food and pharmaceutical industries.